Prognostic capacity of the systemic inflammation response index for functional outcome in patients with aneurysmal subarachnoid hemorrhage - Hou, Yuyang; Fan, Jingxin; Yuan, Huisheng; Zheng, Hu; Yang, Hongkuan; Li, Hua; Chen, Rudong; Yu, Jiasheng (Frontiers in Neurology, 2023)
Objective We aimed to investigate the relationship between systemic inflammatory response index (SIRI) and functional outcome after aneurysmal subarachnoid hemorrhage (aSAH). Methods A retrospective cohort study was performed involving all consecutive aSAH patients admitted to our institution. The modified Rankin Scale (mRS) score was performed to determine the functional outcomes of all patients at 3 months after aSAH. Results were categorized as favorable (mRS score 0–2) and unfavorable (mRS score 3–6). Univariate and multivariate logistic regressive analyses were utilized to identify the prognostic significance of SIRI. To minimize the effects of confounding factors, patients were stratified according to the optimal cut-off value of SIRI with propensity score matching (PSM). Further subgroup analysis was conducted to verify the consistency of our findings and Pearson's correlation analysis was used to assess the relationship between SIRI and the severity of aSAH. Results In this study, 350 patients were enrolled and 126 (36.0%) of them suffered unfavorable outcomes. The SIRI of 5.36 × 109/L was identified as the optimal cut-off value. Two score-matched cohorts (n = 100 in each group) obtained from PSM with low SIRI and high SIRI were used for analysis. A significantly higher unfavorable functional outcome rate was observed in patients with high SIRI before and after PSM (p < 0.001 and 0.017, respectively). Multivariate logistic regression analysis demonstrated that SIRI value ≥ 5.36 × 109/L was an independent risk factor for poor outcomes (OR 3.05 95% CI 1.37–6.78, p = 0.006) after adjusting for possible confounders. A identical result was discovered in the PSM cohort. In ROC analysis, the area under the curve (AUC) of SIRI was 0.774 which shown a better predictive value than other inflammatory markers observed in previous similar studies. Pearson's correlation analysis proved the positive association between SIRI and aSAH severity. Conclusions Elevated SIRI at admission is associated with worse clinical status and poorer functional outcomes among patients with aSAH. SIRI is a useful inflammatory marker with prognostic value for functional outcomes after aSAH.